A machine perspective of atomic defects in scanning transmission electron microscopy. Issue 3 (15th August 2019) - Dan, Jiadong; Zhao, Xiaoxu; Pennycook, Stephen J.
Abstract: Enabled by the advances in aberration‐corrected scanning transmission electron microscopy (STEM), atomic‐resolution real space imaging of materials has allowed a direct structure‐property investigation. Traditional ways of quantitative data analysis suffer from low yield and poor accuracy. New ideas in the field of computer vision and machine learning have provided more momentum to harness the wealth of big data and sophisticated information in STEM data analytics, which has transformed STEM from a localized characterization technique to a macroscopic tool with intelligence. In this review article, we discuss the prime significance of defect topology and density in two‐dimensional (2D) materials, which have proved to be a powerful means to tune a wide range of properties. Subsequently, we systematically review advanced data analysis methods that have demonstrated promising prospects in analyzing STEM data, particularly for identifying structural defects, with high throughput and veracity. A unified framework for atomic structure identification is also summarized. Abstract : The synergy of STEM imaging and machine learning has transformed STEM from a localized characterization technique to a macroscopic tool with intelligence. This review discussed the prime significance of defect topology and density in two‐dimensional (2D) materials and STEM data analytics, particularly for identifying structural defects from STEM images.